Circadian rest-activity patterns in bipolar disorder and borderline personality disorder - McGowan, N; Goodwin, G; Bilderbeck, A; Saunders, K (Springer Nature, 2019)
Bipolar disorder (BD) and borderline personality disorder (BPD) are two psychiatric disorders with overlapping features that can be challenging to separate diagnostically. Growing evidence suggests that circadian rhythm disturbances are associated with psychiatric illness, however circadian patterns of behaviour have not been elucidated in BPD or differentiated from BD. This study compared the circadian structure and timing of rest-activity patterns in BPD with BD and healthy volunteers. Participants with BD (N = 31) and BPD (N = 21) and healthy controls (HC, N = 35) wore an actigraph on their non-dominant wrist for 28 day periods as part of the Automated Monitoring of Symptom Severity (AMoSS) study. Non-parametric circadian rhythm analysis of rest-activity patterns and cosinor analysis of distal temperature rhythms were conducted to elucidate circadian function between groups. Covariates controlled for included employment status, BMI and gender. Compared with HC and BD, individuals with BPD showed significantly delayed phase of night-time rest patterns (“L5 onset”) (mean difference = 1:47 h, P < 0.001; mean difference = 1:38 h, P = 0.009, respectively), and relative to HC showed delayed daytime activity onset (“M10 onset”) (mean difference = 2:13 h, P = 0.048) and delayed temperature phase (mean difference = 1:22 h, P = 0.034). These findings suggest that delayed circadian function may be a clinically important phenotype in individuals with BPD. Future work should interrogate the causality of this association and examine interventions which target delayed circadian function in the treatment of BPD.